A fully-packaged ship-shaped hybrid nanogenerator for blue energy harvesting toward seawater self-desalination and self-powered positioning. (March 2019) - Wang, Heyi; Zhu, Quanyong; Ding, Zhenyu; Li, Zhilei; Zheng, Haiwu; Fu, Jingjing; Diao, Chunli; Zhang, Xinan; Tian, Jianjun; Zi, Yunlong
Abstract: Lately, hybridization of triboelectric nanogenerator (TENG) has shown great potential in collecting ocean-wave energy with low frequency and irregular amplitude, and hybridization of TENG with electromagnetic generator (EMG) can enable the broadband energy harvesting with the fully-packaged design. Here, a ship-shaped hybridized nanogenerator (SHNG) consistsing of three TENGs and an EMG has been proposed, from which the TENGs works in freestanding rolling and contact-separation modes. In this design, the rolling of magnetic cylinder makes the TENG easy to be driven by water wave due to the low frictional resistance. Moreover, the unique structural design is beneficial to the packaging, ensuring the isolation of the SHNG from the external water environment and thus providing stable electrical output. Under an operating frequency of 2 Hz, the contact-separation TENG and EMG are able to produce a peak power of about 800 µW with a resistive load of 20 MΩ and 9 mW with a resistive load of 100 Ω, respectively. In terms of charging capacitors, the SHNG can achieve higher charging voltage and faster charging speed than that of the individual TENG or EMG. To accomplish impedance match between the TENG and EMG, a transformer was employed to decrease the impedance of the TENG. The SHNG has been demonstrated to effectively desalinate seawater, and its desalination rate reaches 29.4% in 3 h. The SHNG has also been proved to power a digital temperature-humidity meter and drive a radio-frequency emitter to form a self-powered wireless positioning system. This work not only renders an innovative approach toward effective blue energy harvesting, but also presents a great prospect for enabling self-desalination and self-powered marine rescue systems. Graphical abstract: fx1 Highlights: A ship-shaped hybrid nanogenerator is constructed with light material, easily driven by water waves. The electric output of the SHNG can be enhanced by combining two energy harvesting methods. A self-desalination system can transform seawater into drinking water. A self-powered wireless positioning system is introduced to get location information for maritime workers.